PENGARUH KETERIKATAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan EfandA 707 Brebes) - Siti Fatimatuz Zahro; Azizah Indriyani; Nur Afridah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This study aims to determine the influence of work attachment and Work Environment on the performance of EfandA 707 employees The population in this study is EfandA 707 employees. The number of samples used was 50 respondents using the saturated sample technique. The research data was tested with validity and reliability tests. The hypothesis test was carried out by multiple linear regression test using SPSS 25.0 software in this study. The results of the analysis showed that the work attachment variable had a positive and significant influence on employee performance (t count = 4.455 > > t table = 1.677, sig = 0.010 < 0.05). The variable of the work environment also had a positive and significant effect on employee performance (t count = 3.394 > t table = 1.677, sig = 0.000 < 0.05). Simultaneously, these three variables have a significant effect on service quality, with an F value of 23.499 which is greater than the F table 2.79 (sig = 0.000 < 0.05). The author suggests to increase vigor, dediction, absorption and immediately improve problems such as lighting, temperature, noise, movement space, work safety and good employee relations with colleagues who are not supportive. By making these improvements, it is hoped that EfandA 707 can achieve better performance levels and improve overall employee satisfaction and well-being.